Biological Synthesis of Monodisperse Uniform-Size Silver Nanoparticles (AgNPs) by Fungal Cell-Free Extracts at Elevated Temperature and pH - Mariana Fuinhas Alves; Patrick G. Murray (Journal of Fungi, 2022)
Fungi’s ability to convert organic materials into bioactive products offers environmentally friendly solutions for diverse industries. In the nanotechnology field, fungi metabolites have been explored for green nanoparticle synthesis. Silver nanoparticle (AgNP) research has grown rapidly over recent years mainly due to the enhanced optical, antimicrobial and anticancer properties of AgNPs, which make them extremely useful in the biomedicine and biotechnology field. However, the biological synthesis mechanism is still not fully established. Therefore, this study aimed to evaluate the combined effect of time, temperature and pH variation in AgNP synthesis using three different fungi phyla (Ascomycota, Basidiomycota and Zygomycota) represented by six different fungi species: Cladophialophora bantiana (C. bantiana), Penicillium antarcticum (P. antarcticum), Trametes versicolor (T. versicolor), Trichoderma martiale (T. martiale), Umbelopsis isabellina (U. isabellina) and Bjerkandera adusta (B. adusta). Ultraviolet–visible (UV-Vis) spectrophotometry and transmission electron microscopy (TEM) results demonstrated the synthesis of AgNPs of different sizes (3 to 17 nm) and dispersity percentages (25 to 95%, within the same size range) using fungi extracts by changing physicochemical reaction parameters. It was observed that higher temperatures (90 °C) associated with basic pH (9 and 12) favoured the synthesis of monodisperse small AgNPs. Previous studies demonstrated enhanced antibacterial and anticancer properties correlated with smaller nanoparticle sizes. Therefore, the biologically synthesised AgNPs shown in this study have potential as sustainable substitutes for chemically made antibacterial and anticancer products. It was also shown that not all fungi species (B. adusta) secrete metabolites capable of reducing silver nitrate (AgNO3) precursors into AgNPs, demonstrating the importance of fungal screening studies.